Kepribadian, Motivasi, Dukungan Keluarga dan Pendidikan terhadap Minat Berwirausaha Mahasiswa Jurusan Akuntansi - Wiadnyana Putra, Cokorda Bagus; Ramantha, I Wayan (E-Jurnal Akuntansi; Vol 31 No 2 (2021)DO - 10.24843/EJA.2021.v31.i02.p05, 2021)
This research was conducted to determine the influence of personality, motivation consisting of career and economic motivation, family support, accounting education and entrepreneurship education on the interest in entrepreneurship in regular accounting students majoring in the Faculty of Economics and Business, Udayana University. The population in this study were students majoring in regular accounting, class 2016. Methods of determining the sample using saturated sampling technique. The sample in this study amounted to 120 people. The data collection method is a survey method with a questionnaire. The data analysis technique is the classical assumption test and multiple linear regression analysis. Based on the results of the analysis, it was found that personality, motivation which includes career and economic motivation, family support, accounting education, and entrepreneurship education have a positive effect on students interest in entrepreneurship in the Bukit regular accounting major. Keywords: Personality; Motivation; Endorsement; Education; Entrepreneurship.